Gender stereotypes in the construction of Fang women: a patriarchal education for submission - Bituga-Nchama, Pedro (2021)
The main objective of this research is to show that gender stereotypes are part of the patriarchal education that Fang women receive. This sociocultural education model is based on submission and dependence, with behavioral guidelines to subject women to the service of men. In such a context, it is not possible to speak of equality because the aptitudes of the woman are undervalued, considering her socioculturally inferior to the man and that, therefore, should remain only in the private sphere. This model of education promoted by the existence of gender stereotypes is a way of socially building the type of woman that society needs. For this reason, the proposed solution is to dismantle the gender stereotypes that constitute the social obstacles created by patriarchy, in order to exclusively favor men to the detriment of women. The method used in this research is explanatory-descriptive, based on the qualitative methodology, based on the bibliographic review and direct observation on the situation of women in the Fang culture, in terms of gender stereotypes. The results achieved with this study show that the empowerment of women is necessary to get out of the everlasting status quo in which she finds herself due to the sociocultural education that has been instilled in her. For this reason, the very voices of the Fang women, demand from the feminist groups, a total dismantling of this patriarchal educational model